Catechins inhibit atherosclerosis in male rats on a high fat diet - Erna Susanti; Achmad Rudijanto; Retty Ratnawati (Faculty of Medicine, Universitas Trisakti, 2012)
BackgroundA catechin isolate from the green tea clone GMB 4, which shows antioxidant activity, may be a candidate drug for prevention of atherosclerosis. The aim of this study was to analyze the effect of catechin on endothelial nitric oxide synthase (eNOS) and p110 phosphoinositide 3-kinase inhibitor (PI3K) expression and on p38 mitogen activated protein kinase (MAPK) activity in male rats fed a high fat diet.MethodsTwenty five male Wistar rats were divided into the following five groups: rats on standard diet; rats on high fat diet; rats on high fat diet + catechin 3 mg/day; rats on high fat diet + catechin 6 mg/day; and rats on high fat diet + catechin 24 mg/day. eNOS and p110 PI3K expression and p38 MAPK activity were measured by means of ELISA. ResultsHigh fat diet significantly increased eNOS expression, decreased p110 PI3K expression, and increased p38 MAPK activity in male rats, in comparison with standard diet (p<0.05). Administration of 3 mg/day catechin decreased eNOS expression compared to that in the high fat diet group without catechin (p<0.05). The administration of catechin increased p100 PI3K expression to a similar extent as that in the high fat diet groups with catechin 6 mg/day and 24 mg/day. Administration of catechin at all doses decreased p38 MAPK activity to the level of the standard diet group. ConclusionsHigh fat diet increases eNOS expression, decreases PI3K expression, and increases p38 MAPK activity. Administration of catechin decreases eNOS expression, increases PI3K expression, and decreases p38 MAPK activity.